The use of low frequencies in a full‐waveform inversion and impedance inversion land seismic case study. (27th February 2013) - Baeten, Guido; de Maag, Jan Willem; Plessix, René‐Edouard; Klaassen, Rini; Qureshi, Tahira; Kleemeyer, Maren; Kroode, Fons ten; Rujie, Zhang
ABSTRACT Velocity model building and impedance inversion generally suffer from a lack of intermediate wavenumber content in seismic data. Intermediate wavenumbers may be retrieved directly from seismic data sets if enough low frequencies are recorded. Over the past years, improvements in acquisition have allowed us to obtain seismic data with a broader frequency spectrum. To illustrate the benefits of broadband acquisition, notably the recording of low frequencies, we discuss the inversion of land seismic data acquired in Inner Mongolia, China. This data set contains frequencies from 1.5–80 Hz. We show that the velocity estimate based on an acoustic full‐waveform inversion approach is superior to one obtained from reflection traveltime inversion because after full‐waveform inversion the background velocity conforms to geology. We also illustrate the added value of low frequencies in an impedance estimate.